Practical MATLAB : with modeling, simulation, and processing projects - Turk, Irfan (Apress, 2019)
Apply MATLAB programming to the mathematical modeling of real-life problems from a wide range of topics. This pragmatic book shows you how to solve your programming problems, starting with a brief primer on MATLAB and the fundamentals of the MATLAB programming language. Then, youll build fully working examples and computational models found in the financial, engineering, and scientific sectors. As part of this section, youll cover signal and image processing, as well as GUIs. After reading and using Practical MATLAB and its accompanying source code, youll have the practical know-how and code to apply to your own MATLAB programming projects. You will: Discover the fundamentals of MATLAB and how to get started with it for problem solving Apply MATLAB to a variety of problems and case studies Carry out economic and financial modeling with MATLAB, including option pricing and compound interest Use MATLAB for simulation problems such as coin flips, dice rolling, random walks, and traffic flows Solve computational biology problems with MATLAB Implement signal processing with MATLAB, including currents, Fast Fourier Transforms (FFTs), and harmonic analysis Process images with filters and edge detection Build applications with GUIs.